Characterization of oil palm empty fruit fiber reinforced PVA / Ramin Solouki Bonab - Ramin, Solouki Bonab (2013)
Fiber reinforced polymers (FRP) are kinds of composites commonly used for increasing the strength, elasticity and tribological properties of material. The composition of polymers and fibers make it as a unique property and provide solution to the ever growing concerns regarding cost, environment and structural stability of beams and columns. Development of polymer made life easier and comfortable and introduce new life to human but recycling polymer is today’s issue. It is true that polymers are recyclable but process of recycling polymers require greater processing such as heat treating, thermal depolymerization and monomer recycling to be recycle due to high molecular weight of their large polymer chain. Polyethylene and polypropylene plastic products such as bags, film and packaging to degrade totally and harmlessly after use, thereby providing the best environmental solution to the plastic pollution problem, at little or no extra cost. So, Eco-polymers provide managerial, technical, marketing and logistical resources and support necessary to ensure efficient and cost-effective. For achieving best efficient of mechanical and thermal properties of polymers is reinforcement and additive some material and fibers. Furthermore, this method is cost-effective due to improving and deriving high quality polymer from cheaper ones. The matrix is often reinforced by stronger and stiffer reinforcing fibers such as carbon, glass. In this project we set to investigate high hardness and factors which effect on mechanical properties, study thermal analysis and some general tests such as chemical resistance, water absorption and void content by using raw data we aim to analyses the process to improve property of polymers.